The dynamics of histamine level in patients with chronic urticaria under the influence of different methods of treatment. - Dytyatkovska Ye.M. (Medičnì Perspektivi)
There was studied the efficiency of different methods of chronic urticaria treatment. All patients were divided into 2 groups depending on treatment scteme. The paper shows the dynamics of histamine level in blood plasma, intestine disbiosis in patients with chronic urticaria under the influence of different treatment complexes. It was proved that there exists the correlation between the serum histamine level and method of treatment. Intro¬ducing bionorm into the treatment allows to decrease histamine level and correspondingly to significantly improve clinical effect and patients’ life quality.